The prevalence of Intraabdominal hypertension and its association with mortality in post emergency laparotomy at Hospital Tengku Ampuan Afzan (HTAA), Kuantan - Mohd. Wazir Mohd. Azzam (Kulliyyah of Medicine, International Islamic University Malaysia, 2017)
The purpose of this study was to measure the prevalence of Intraabdominal hypertension (IAH) and its complications in relation to mortality rate. A double-blind prospective study of all post emergency laparotomy general surgical patients in ICU HTAA, Kuantan from June 2014-June 2015. Intraabdominal pressure (IAP) was measured by intravesicular technique using a manometry; taken once daily (first reading within 24 hours of admission). If IAP exceeds 10mmHg, 2 subsequent readings were taken 4 to 6 hours apart. Data included the demographics, clinical, Sequential Organ Failure Assessment (SOFA) score and Acute Physiology And Chronic Health Evaluation II (APACHE II) score . We enrolled 51 patients, age of the subjects range from 14 to 82 with mean of age at 49.22 ± 17.35. Prevalence of IAH was 73% and 18% had abdominal compartment syndrome (ACS). Mean for SOFA and APACHE II score were 8.10 ± 4.920 and 14.57 ± 6.152, respectively. IAH (p=0.067), per se was found to be not associated with mortality but was associated with Acute Kidney Injury or Renal replacement Therapy (p=0.037), duration in ICU (p=0.005), duration on ventilator (p=0.005) and Max SOFA score (p=0.006). ACS (p=0.001) was found to have significant association to mortality, Acute Kidney Injury or Renal replacement Therapy (p=0.037), duration in ICU (p=0.044), duration on ventilator (p=0.024), Max SOFA score (p=<0.001), and higher surgical experience (p=0.009). The factors associated to mortality in this study were presence of AKI or RRT (p=0.001), duration on ventilator (p=0.021), SOFA score (p=0.001), and APACHE II score (p=0.003). Post laparotomy patients have a higher probability of developing IAH and ACS in this study. This furthermore stresses the importance of monitoring of IAH/IAP, in order to provide a timely identification, treatment and management of IAH in order to reduce the complications of organ dysfunction and ACS, and thus reducing the mortality rate.